The Effect of the Family Training Program on Married Women's Couple-Burnout Levels - Sirin, Hatice Deveci; Deniz, M. Engin (EDAM, 2016)
This study aims to investigate the effect of Modules 2 and 3 of the Family Communication Section of the Family Training Program as prepared by the Ministry of Family and Social Policies on married women's couple-burnout levels. The study group consists of 40 married women in total: 20 constituting the experimental group and the remaining 20 constituting the control group. Each session lasted approximately 120 minutes, and the program continued for 12 weeks. Research data were collected using the Couple Burnout Measure. A randomized pretest-posttest control design was used in the study. At the end of the sessions, the Mann-Whitney U test was used to determine whether there was a difference between the mean pretest and posttest scores of the Couple Burnout Measure for the experimental and control groups; the Wilcoxon signed-rank test was used to detect any significant difference among the mean pretest, posttest, and follow-up test scores. According to the findings, Modules 2 and 3 of the Family Communication Section of the Family Training Program were determined to help decrease married women's couple-burnout levels. The couple-burnout posttest scores for the women who had participated in the program were seen to be lower compared to those who had not taken part in the program. Additionally, the posttest scores for the women in the experimental group were found to be significantly lower than their pretest scores. No significant difference between the pretest and posttest scores of women in the control group was found. The positive effect observed on the experimental group was determined to last for two months (eight weeks). The obtained findings were interpreted in light of the literature, and suggestions have been presented.
Keywords: Family training program; Couple burnout; Married women; Marriage; Family; EDUCATION; COMMUNICATION; Education & Educational Research